Keefektifan Pelatihan Pembuatan Worksheet Interaktif dengan Wizer.Me untuk Mengoptimalkan Pembelajaran di SDN 26 Mataram - Dyah Indraswati; Muhammad Sobri; Asri Fauzi; Lalu Wira Zain Amrullah; Aisa Nikmah Rahmatih (Departement of Mathematics Education, 2023)
This study aims to determine the effectiveness of training in making interactive worksheets with Wizer. me on the ability and knowledge of SDN 26 Mataram teachers in making interactive worksheets. This research is quantitative research with a pre-experimental design type one group pretest-posttest. This research includes population research because all 12 teachers are the research subjects. The instrument used was 10 multiple choice questions which were used as pretest and posttest questions. The data analysis technique used a normality test as a prerequisite for analysis, paired sample t-test, an effect size test, and an N-Gain test. All data are normally distributed as indicated by the normality test. The paired sample t-test test shows that there is a difference between the pretest and posttest values ​​where the posttest value is higher than the pretest value. The average value of the N-Gain score is 45.6944 or 46% (less effective). The minimum N-gain score is 0 and the maximum is 83.33%. The conclusion is that training on making interactive worksheets with Wizer. me is less effective in improving the skills and knowledge of SDN 26 teachers in making interactive worksheets.